The Effect of Glycomacropeptide versus Amino Acids on Phenylalanine and Tyrosine Variability over 24 Hours in Children with PKU: A Randomized Controlled Trial - Daly, Anne (2019)
Introduction: In phenylketonuria (PKU), evidence suggests that casein glycomacropeptide supplemented with rate-limiting amino acids (CGMP-AA) is associated with better protein utilisation and less blood phenylalanine (Phe) variability. Aim: To study the impact of CGMP-AA on blood Phe variability using 3 different dietary regimens in children with PKU. Methods: This was a 6-week randomised controlled cross-over study comparing CGMP-AA vs. Phe-free l-amino acids (l-AA) assessing blood Phe and tyrosine (Tyr) variability over 24 h in 19 children (7 boys) with PKU, with a median age of 10 years (6⁻16). Subjects were randomised to 3 dietary regimens: (1) R1, CGMP-AA and usual dietary Phe (CGMP + Phe); (2) R2, CGMP-AA - Phe content of CGMP-AA from usual diet (CGMP - Phe); and (3) R3, l-AA and usual dietary Phe. Each regimen was administered for 14 days. Over the last 48 h on days 13 and 14, blood spots were collected every 4 h at 08 h, 12 h, 16 h, 20 h, 24 h, and 04 h. Isocaloric intake and the same meal plan and protein substitute dosage at standardised times were maintained when blood spots were collected. Results: Eighteen children completed the study. Median Phe concentrations over 24 h for each group were (range) R1, 290 (30⁻580), R2, 220 (10⁻670), R3, 165 (10⁻640) μmol/L. R1 vs. R2 and R1 vs. R3 p < 0.0001; R2 vs. R3 p = 0.0009. There was a significant difference in median Phe at each time point between R1 vs. R2, p = 0.0027 and R1 vs. R3, p < 0.0001, but not between any time points for R2 vs. R3. Tyr was significantly higher in both R1 and R2 [70 (20⁻240 μmol/L] compared to R3 [60 (10⁻200) μmol/L]. In children < 12 years, blood Phe remained in the target range (120⁻360 μmol/L), over 24 h, for 75% of the time in R1, 72% in R2 and 64% in R3; for children aged ≥ 12 years, blood Phe was in target range (120⁻600 μmol/L) in R1 and R2 for 100% of the time, but 64% in R3. Conclusions: The residual Phe in CGMP-AA increased blood Phe concentration in children. CGMP-AA appears to give less blood Phe variability compared to l-AA, but this effect may be masked by the increased blood Phe concentrations associated with its Phe contribution. Reducing dietary Phe intake to compensate for CGMP-AA Phe content may help.